2011
DOI: 10.1128/jcm.06092-11
|View full text |Cite
|
Sign up to set email alerts
|

True Microbiota Involved in Chronic Lung Infection of Cystic Fibrosis Patients Found by Culturing and 16S rRNA Gene Analysis

Abstract: Patients suffering from cystic fibrosis (CF) develop chronic lung infection. In this study, we investigated the microorganisms present in transplanted CF lungs (n ‫؍‬ 5) by standard culturing and 16S rRNA gene analysis. A correspondence between culturing and the molecular methods was observed. In conclusion, standard culturing seems reliable for the identification of the dominating pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
2
36
0
1
Order By: Relevance
“…For CF patients, a notably high species diversity for the families Prevotellaceae and Streptococcaceae was recently described, which matches the outcome of our study (31). CF end-stage lungs have been shown to harbor relatively low numbers of species, and 16S rRNA gene analysis of explanted lung tissue samples revealed the same four phyla of the five bacterial classes with more than one OTU found in the current study: Proteobacteria, Bacteroidia, Firmicutes, and Actinobacteria (32). Great similarity was observed between the dominant OTUs in the current and other studies; therefore, the communities in CF airways are presumably greatly influenced by these species, e.g., P. aeruginosa, S. aureus, Rothia mucilaginosa, and Streptococcus spp.…”
Section: Discussionsupporting
confidence: 76%
“…For CF patients, a notably high species diversity for the families Prevotellaceae and Streptococcaceae was recently described, which matches the outcome of our study (31). CF end-stage lungs have been shown to harbor relatively low numbers of species, and 16S rRNA gene analysis of explanted lung tissue samples revealed the same four phyla of the five bacterial classes with more than one OTU found in the current study: Proteobacteria, Bacteroidia, Firmicutes, and Actinobacteria (32). Great similarity was observed between the dominant OTUs in the current and other studies; therefore, the communities in CF airways are presumably greatly influenced by these species, e.g., P. aeruginosa, S. aureus, Rothia mucilaginosa, and Streptococcus spp.…”
Section: Discussionsupporting
confidence: 76%
“…However, the experience of patients with CF in our center indicates that classic culture methods sufficiently detects the clinically important bacteria. 73 Moreover, PCR detects a broad variety of bacteria but may blur which bacteria are relevant to treat.…”
Section: *Of a Total Of 8 Patients The Number Of Times The Bacteria mentioning
confidence: 99%
“…However, with the development of culture-independent molecular screening technique, it is now evident that microbes can also be found residing within the lower respiratory tract, albeit at a lower biomass when compared to the upper respiratory tract [14,26]. There are studies that have demonstrated that the lower airway tract microbiome could be misrepresented due to upper respiratory tract microbial flora contamination during the sample collection process [27,28]. Therefore, microbial study on the lower airway tract is a fledging area of interest with many challenges.…”
Section: Lower Respiratory Tractmentioning
confidence: 99%
“…A significant number of the disease-specific studies are concentrated on cystic fibrosis [27,28,46,48,49,51,52], signifying the need to redirect research efforts on the less well-studied areas such as asthma, COPD and RTI.…”
Section: Overview Of Human Airway Tract Microbiome Studiesmentioning
confidence: 99%